(untitled) (Herald of Journalism, 2020)
Publicists XIX century Muhammad Salih Babadjanov and Сhokan Va- likhanov – extraordinary and vibrant personality, who made a significant contribution to the transformation of Kazakhstan at the time. These two public figures in journalism revealed urgent problems of the Kazakh soci- ety. If M-S.Babadzhanov presented life of the Kazakh people, mostly living in the West Kazakhstan. That Сh.Valihanov investigated native people of Eastern Kazakhstan.